Current status on microsatellite instability, prognosis and adjuvant therapy in colon cancer: A nationwide survey of medical oncologists, colorectal surgeons and gastrointestinal pathologists. Issue 1 (8th October 2020) - Toh, James W. T.; Mahajan, Hema; Chapuis, Pierre; Spring, Kevin
Abstract: Background: There is significant variation in attitude both towards the role of microsatellite instability (MSI) in predicting prognosis, and towards its role in guiding which Stage II colon cancer patients may benefit from adjuvant chemotherapy. Aim: To examine the current status of specialist attitudes towards MSI in guiding prognosis and adjuvant therapy in stage II colon cancer. Methods: The Pathology in Colon Cancer, Prognosis and Uptake of Adjuvant Therapy (PiCC UP) Australia and New Zealand questionnaire was distributed to colorectal surgeons, medical oncologists and pathologists after institutional board approval. A 5‐scale Likert score was used to assess attitudes towards 23 pathological features for prognosis and 18 features for adjuvant therapy. Data were analysed using a rating scale and graded response model in item response theory (IRT) on STATA (Stata MP, version 15; StataCorp LP). Results: 164 specialists (45 oncologists, 86 surgeons and 33 pathologists) participated. 80.5% regularly attended colorectal multidisciplinary team (MDT) meetings. 89.63% and 59.26% of specialists reported that MSI status was likely or definitely to influence prognosis in colon cancer and recommendations for adjuvant therapy in Stage II colon cancer respectively. IRT modelling was achieved in 17 pathological features for prognosis. MSI IRT score was 4.47 (95% CI: 4.05‐4.68). IRT modelling was achieved in 10 pathological features for adjuvant therapy. MSI IRT score was 3.62 (2.89‐4.15). MSI ranked 10 (of 17) in order of importance in determining prognosis and ranked three (of 10) in guiding adjuvant therapy. Conclusion: MSI status is considered an important biomarker when selecting patients for adjuvant therapy in Stage II colon cancer. MSI is also considered useful in prognostication of colon cancer. MSI status was ranked similar to the tumour grade of differentiation and the presence of perineural invasion. Abstract :